Natural Pest Control: Effectiveness of Strychnos nux-vomica Extracts in Rice Protection - P, Dhanapal.; V, Ramesh. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The efficacy of Strychnos nux-vomica seed, bark, and leaf extracts was evaluated against two major rice pests, Cnaphalocrocismedinalis (rice leaf folder) and Nilaparvatalugens (brown planthopper), under Rabi and Kharif conditions. Field trials demonstrated a significant reduction in pest infestation and increased mortality rates with higher extract concentrations. Among the tested formulations, the seed extract at 1.25% concentration exhibited the highest insecticidal activity, achieving 52.16% and 80.58% mortality against C. medinalis and N. lugens, respectively. The bark and leaf extracts were also effective, with mortality rates reaching 50.57% and 54.95% for C. medinalis and 76.54% and 64.26% for N. lugens. In contrast, untreated control plots recorded substantially higher pest populations, underscoring the efficacy of S. nux-vomica extracts as biopesticides. These findings highlight the potential of S. nux-vomica, particularly its seed extract, as a sustainable and eco-friendly alternative to synthetic pesticides for integrated pest management in rice cultivation.